2020
DOI: 10.1051/e3sconf/202017801047
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between operational properties of peat heat-insulating materials and the content of mineral binders in them

Abstract: This work presents the main results of calculation and experimental study on relation between the operational properties of peat heat-insulating materials (HIM) and the content of mineral binders in them aiming at reducing heat energy costs by energy-consuming objects. It was experimentally proved that introduction of cement increases thermal conductivity, and introduction of calcium oxide as a mineral binder, on the contrary, promotes the development of material porosity while maintaining strength cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
1
3
0
1
Order By: Relevance
“…These characteristics are also comparable with the characteristics of thermal insulation material made of low-moor peat with binder, frame component (wooden aggregate), and additive (Vasiļjeva and Korjakins, 2017). Our previous studies (Sinitsyn et al, 2020; have shown that introducing a three-component polymer into a composite mixture consisting of high-lying peat, sawdust and gypsum increases mechanical strength while decreasing average density and thermal conductivity. However, further testing showed that the polymer engulfs the gypsum, peat, and sawdust particles, causing a gradual decrease in porosity during the formation of a solid structure.…”
Section: Figure 5 Relationship Between Product Yield and High-lying Psupporting
confidence: 74%
“…These characteristics are also comparable with the characteristics of thermal insulation material made of low-moor peat with binder, frame component (wooden aggregate), and additive (Vasiļjeva and Korjakins, 2017). Our previous studies (Sinitsyn et al, 2020; have shown that introducing a three-component polymer into a composite mixture consisting of high-lying peat, sawdust and gypsum increases mechanical strength while decreasing average density and thermal conductivity. However, further testing showed that the polymer engulfs the gypsum, peat, and sawdust particles, causing a gradual decrease in porosity during the formation of a solid structure.…”
Section: Figure 5 Relationship Between Product Yield and High-lying Psupporting
confidence: 74%
“…Using different methods, peat can produce thermal insulation and raw materials in various construction materials substrates, and pharmaceutical products [152][153][154][155][156]. Also, an agro-industrial resource, peat, has a high but not fully used potential [57,58].…”
Section: Technologies and Technological Processes In Peat Processingmentioning
confidence: 99%
“…Peat soil can be a promising addi-tive in construction materials, strengthening the durability of masonry blocks to meet necessary building standards. It is possible to improve building materials' characteristics, including insulation properties, using peat as an additive or producing the products themselves [99,[152][153][154][155][156]. In building materials, cement has often been used with high-lying peat, moistening peat with water first.…”
Section: Building Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…При производстве ТИМ с применением кремнийорганических полимеров в качестве вяжущих и природных теплоизоляторов используют низинный торф, в том числе из торфяников Грязовецкого и Вологодского районов Вологодской области [13]. Степень гумификации верховой торф составляет 14…16 % (слаборазложившийся); низинного -39 % (сильноразложившийся).…”
unclassified